Adapting agent technology in managing requirements reuse process - Wan Jusoh, Wan Nursyamsiah (2017)
Requirement Engineering (RE) is a process to define, document and maintain software requirements. Requirement process involve a great deal of works from requirement elicitation to requirement documentation, thus reuse requirements become an alternative to speed up the process. Requirements reuse is an approach to use existing requirements documents to reduce the general effort inside Software Development Life Cycle (SDLC). However proper approach for small-sized enterprises is not adequately explored. Hence improvement and systematic management approach is required for requirements reuse in small-sized enterprises. A model develop by a team of research on software requirements catalog only focus on functional requirements. As such this research propose a well-defined and mature reuse methods by integrating non-functional requirements in the model. The first part of this project study the requirements reuse process and existing models. In the next activity, a new model is proposed to include non-functional requirements in the process. Lastly a prototype is developed by implementing agent technology and evaluation is done to prove the quality of requirements reuse. The results show that the proposed model have a better quality compared to previous model. As correct requirements prevent software failure, it will assist in delivering a successful software and shorten the SDLC.